Centralised revenue redistribution as a potential cause of internal conflict in Kenya - Latif, Lyla (University of Hradec Králové, 2016)
This article argues that when a large part of a population has either limited or no access to social and economic resources as a result of government policy in redistributing revenue towards the capital, such concentrated redistribution at the centralised level may become a key factor in sparking internal conflicts among the population living outside the capital. A state that does not share the national wealth and resource revenues equitably among its citizens therefore provides a platform to those who want to challenge the legitimacy of the state to engage in violence. Thus, the centralisation of revenue redistribution by a state may be seen as a potential factor that may lead to internal conflict especially in circumstances where high levels of poverty and unemployment in the country are widespread. Although such internal conflict may not necessarily be violent, centralised revenue redistribution may cause an uprising among the population and lead to a substantial change in the form of government, moving it from a centralised to a decentralised form of government in order to appease the population and for the state to retain its legitimacy. Such was the case in Kenya.